Analysis of Groundwater Advance Decline in Surakarta City - Cholil, Munawar (Forum Geografi, 1998)
This research was intended to know the cause of a drawdown of artesian groundwater surface and analyze on exploiting its groundwater in Surakarta. The total amount of groundwater exploitation in Surakarta will be 69,206.4 m3Â if it is compared the groundwater runoff capacity of unconfined aquifer as with 8,860.9 m3 a day and confined aquifer as 42,447.3 m3 a day. Thus, the total amount of groundwater runoff in Surakarta is 51,308.2 m3 a day. Groundwater exploitation has exceeded the capacity of groundwater runoff as 17,898.2 m3, so the reservoir of groundwater is going to reduce continually. Groundwater exploitation in the loation of the researh has caused a piezometric drawdown. In 1990, its piezometric was negative, it means that the position of the piezometric was under the surface of land, while in 1990Â artesian well indicated that its piezometric was almost nearly positive. Thus, the piezometric drawdown average 9.4 m3. In the center of the ity, it happened the cone of depression at piezometric contour in 1990, so a piezometric drawdown that resulted from groundwater exploitation exceeding the runoff of groundwater was proved. As a result of groundwater exploitation excessively, it resulted in the inequilibrium of groundwater. This depession has been extending continually as a result of adding wells, so it result in a groundwater drawdown permanently, as happened in the location of the research.